Controlling the Surface Oxidation of Cu Nanowires Improves Their Catalytic Selectivity and Stability toward C2+ Products in CO2 Reduction. (20th November 2020) - Lyu, Zhiheng; Zhu, Shangqian; Xie, Minghao; Zhang, Yu; Chen, Zitao; Chen, Ruhui; Tian, Mengkun; Chi, Miaofang; Shao, Minhua; Xia, Younan
Abstract: Copper nanostructures are promising catalysts for the electrochemical reduction of CO2 because of their unique ability to produce a large proportion of multi‐carbon products. Despite great progress, the selectivity and stability of such catalysts still need to be substantially improved. Here, we demonstrate that controlling the surface oxidation of Cu nanowires (CuNWs) can greatly improve their C2+ selectivity and stability. Specifically, we achieve a faradaic efficiency as high as 57.7 and 52.0 % for ethylene when the CuNWs are oxidized by the O2 from air and aqueous H2 O2, respectively, and both of them show hydrogen selectivity below 12 %. The high yields of C2+ products can be mainly attributed to the increase in surface roughness and the generation of defects and cavities during the electrochemical reduction of the oxide layer. Our results also indicate that the formation of a relatively thick, smooth oxide sheath can improve the catalytic stability by mitigating the fragmentation issue. Abstract : In the electrochemical reduction of CO2, faradaic efficiencies as high as 57.7 and 52.0 % are achieved for ethylene when Cu nanowires oxidized by the O2 from air (A‐CuNWs) and aqueous H2 O2 (H‐CuNWs) serve as catalysts, respectively. The increased surface roughness greatly enhances the C2+ selectivity of the catalysts, and the formation of a relatively thick, smooth oxide sheath can improve the catalytic stability.